Simuliranje odgovora zadrževalnega hrama jedrske elektrarne med veliko izlivno nezgodo - Kljenak, Ivo (Strojniški vestnik, 2000)
Containment phenomena during a large-break loss-of-coolant accident in a two-loop pressurized-water reactor nuclear power plant were simulated withn theCONTAIN thermal-hydraulic computer code. Pressure and temperature responses as well as coolant and energy distributions were analyzed.
Keywords: jedrska tehnika; jedrska varnost; simulacije; nezgode; izliv; zadrževalni hram